Mathematical Modelling and Field Study of Unsteady Flow in an Irrigation Canal System - Rijo, Manuel (1992)
A computer model for simulation of upstream controlled canal systems, based on the Saint-Venant system of equations, was developed. The system of equations are solved by a four-point linear finite-difference implicit scheme, weighted in time and space. The final linear system of equations is solved by the double-sweep algorithm. The model, a stability and sensitivity analysis of the numerical method are presented as well as the model calibration and verification for the canal network of the Sorraia Irrigation Project, Portugal